2016
DOI: 10.3390/ijms17030424
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of miRNAs in the Drug Resistance of Gastric Cancer

Abstract: Gastric cancer is the third leading cause of cancer mortality worldwide. Unfortunately, most gastric cancer cases are diagnosed in an advanced, non-curable stage and with a limited response to chemotherapy. Drug resistance is one of the most important causes of therapy failure in gastric cancer patients. Although the mechanisms of drug resistance have been broadly studied, the regulation of these mechanisms has not been completely understood. Accumulating evidence has recently highlighted the role of microRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 88 publications
1
83
0
Order By: Relevance
“…These results indicated that overexpression of miR-382 was able to increase the anti-tumor effect of γδ T cells on HCC in vivo. [23][24][25]. Among these miRNAs, miR-382 which acts as a tumor suppressor is reported to inhibit tumor growth and sensitize cancer cells to anti-tumor drugs.…”
Section: Mir-382-overexpressed Hcc Model Is Sensitive To γδ T Cells Tmentioning
confidence: 99%
“…These results indicated that overexpression of miR-382 was able to increase the anti-tumor effect of γδ T cells on HCC in vivo. [23][24][25]. Among these miRNAs, miR-382 which acts as a tumor suppressor is reported to inhibit tumor growth and sensitize cancer cells to anti-tumor drugs.…”
Section: Mir-382-overexpressed Hcc Model Is Sensitive To γδ T Cells Tmentioning
confidence: 99%
“…Conversely, tumor-suppressor miRNAs repress the expression of genes with oncogenic functions [13]. Therefore, RNA has been targeted for the study of new drugs and therapeutic methods [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…miRs have been drawn recently in the development of drug resistance because of their regulatory role in cell homeostasis [48]. Thus, monitoring their association with treatment response along with disease progression is fundamental.…”
Section: Discussionmentioning
confidence: 99%